Optimization of static field homogeneity in human brain using diamagnetic passive shims. - Wilson, J; Jenkinson, M; Jezzard, P (2002)
These preliminary studies demonstrate that static field inhomogeneity in the human inferior frontal cortex (IFC) is significantly diminished through placement of a small amount of strongly diamagnetic material in the roof of the mouth. As a result, susceptibility-related image artifacts in this region, as observed in blood oxygen level dependent (BOLD) functional MRI (fMRI), are considerably decreased without compromising the spatial or temporal resolution of the study. Simulations of the static field utilizing perturbation theory are shown, which support the experimental results. The limitations and possible future developments of the technique are described. The application of diamagnetic passive shimming on other regions of the brain is also discussed. Routine use of the proposed method within fMRI studies is practicable through subject-specific optimization of the technique utilizing the simulation algorithm.